Simulation and animation of locomotion of fictional creatures. - Toh, Wei Ping. (2011)
This project is an attempt at formulation of general methods to simulate the locomotion of multi-legged creatures. Adapting studies ranging from biological mechanics to robotics, this project consolidates various similar concepts proposed and methods which are intuitively logical, to construct a method of simulating and animating the locomotion of multi-legged creatures. Using a test creature of ten legs, motion and control modules are developed. It was found that without realistic parameters, the spring-force motion model yields unrealistic locomotion. Hence, a feasible motion module was developed intuitively through modelling after inverted pendulums.